2018
DOI: 10.1007/s10557-018-6823-9
|View full text |Cite
|
Sign up to set email alerts
|

High Bleeding Risk Patients Treated with Very Thin-Strut Biodegradable Polymer or Thin-Strut Durable Polymer Drug-Eluting Stents in the BIO-RESORT Trial

Abstract: PurposePatients with high bleeding risk (HBR) who undergo percutaneous coronary intervention also have an increased risk of ischemic events and represent an overall high-risk population. The coating of durable polymer drug-eluting stents (DP-DES) may induce inflammation and delay arterial healing, which might be reduced by novel biodegradable polymer DES (BP-DES). We aimed to evaluate the safety and efficacy of treating HBR patients with very thin-strut BP-DES versus thin-strut DP-DES.MethodsParticipants in BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It should be noted that the SENIOR trial protocol used 1‐month DAPT in chronic coronary syndrome and 6‐months DAPT in ACS, even though the Synergy DES had better significant outcomes (especially regarding TVR and TLR) in the overall analysis and in the 1‐month regimen either with meta‐regression and with only 1‐month DAPT trials (Supporting Information: Appendix), yet the thrombotic risk in the chronic setting could be less reliable 12 . The same DES was also used in the HBR analysis of the BIO‐RESORT trial, but it wasn't the only used in more than one trial, neither it has a disproportionate number of observations that could affect our analysis 15 . In fact, 932 patient received Synergy DES in 2 trials meanwhile 2214 patient received BioFreedom in LEADERS FREE and ONYX ONE trials and 1003 patients received Onyx DES in one trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that the SENIOR trial protocol used 1‐month DAPT in chronic coronary syndrome and 6‐months DAPT in ACS, even though the Synergy DES had better significant outcomes (especially regarding TVR and TLR) in the overall analysis and in the 1‐month regimen either with meta‐regression and with only 1‐month DAPT trials (Supporting Information: Appendix), yet the thrombotic risk in the chronic setting could be less reliable 12 . The same DES was also used in the HBR analysis of the BIO‐RESORT trial, but it wasn't the only used in more than one trial, neither it has a disproportionate number of observations that could affect our analysis 15 . In fact, 932 patient received Synergy DES in 2 trials meanwhile 2214 patient received BioFreedom in LEADERS FREE and ONYX ONE trials and 1003 patients received Onyx DES in one trial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we considered for our analysis the following trials: ONYX-ONE, LEADERS FREE, the subanalysis of HBR patients in the BIO-RESORT and SENIOR (divided among ACS and CCS patients). [12][13][14][15] From each study we extracted the following data: author, year of publication, sample size, latest follow-up, baseline clinical features such as age, sex, the proportion of patients with history of diabetes, hypertension, hyperlipidemia, transient ischemic attack, myocardial infarction, PCI, intracerebral hemorrhage, coronary artery bypass graft, chronic kidney disease (CKD) and anemia, the indication for PCI (for example, ACS or STEMI), procedural features (type of stent, stent number, multivessel disease, bifurcation, CTO, lesion length) and medical treatment (DAPT type and duration, oral anticoagulation…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zocca et al demonstrated that BP-DES showed similar safety and efficacy compared with DP-DES in patients with HBR undergoing PCI. 28 Previous meta-analysis has not assessed DAPT duration at patients with HBR. In our study, further analysis showed that, in patients with HBR, # 3-month DAPT significantly reduced the risk of major bleeding and any bleeding and did not increase the risk of ischemic complications, including myocardial infarction, stent thrombosis, and stroke, compared with standard DAPT.…”
Section: Discussionmentioning
confidence: 99%
“…Zocca et al demonstrated that BP-DES showed similar safety and efficacy compared with DP-DES in patients with HBR undergoing PCI. 28…”
Section: Discussionmentioning
confidence: 99%